Evaluation of Power Consumption Minimization Approaches for Autonomous Electronic Equipment - Suzdalenko, Alexander; Galkin, Ilya (Electrical, Control and Communication Engineering, 2011)
The use of electronic data logging device is studied for energy minimization approaches. The energy harvesting elements are described and specific design of power supply unit is provided. The main focus is on the minimization of energy loses at conversion and storage stages, as well as software optimisation is discussed, allowing to prolong the autonomous operation of the electronic device. The example of optimized data logger design is presented.